A new bathyal species of Pardaliscoides (Amphipoda, Amphilochidea, Pardaliscidae) from off the southwestern Gulf of Mexico - Ortiz, M.; Winfield, I.; Ardisson, P.l. (Zootaxa, 2023)
A new species of pardaliscid amphipod is described and illustrated from a single male specimen collected from bathyal sediments (2125 m depth) in the southern Gulf of Mexico. The new species is morphologically closest to Pardaliscoides fictotelson Barnard, 1966, previously documented from Southern California, at 218 m depth. The new pardaliscid differs from other species in the genus in having antenna 1 with a 10-articulate accessory flagellum; maxilliped palp very long; pereopods 5–7 elongate, slender; basis pereopod 7 expanded; telson with a short U–shaped cleft and pointed lobes; uropods 1–2 outer ramus curved, peduncle flat, longer than rami; uropod 3 rami flat, fleshy-lined, with marginal distal short robust setae. An identification key for all known species in the Pardaliscoides genus is also provided. The new species increase the number of Pardaliscoides species documented to six worldwide.